2002
DOI: 10.1097/00004836-200202000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Helicobacter pylori Infection and the Long-term Outcome of Peptic Ulcer After Successful Eradication in Japan

Abstract: Recurrence of peptic ulcer after successful eradication of Helicobacter pylori is closely associated with reinfection. The aim of this study was to examine the recurrence of peptic ulcer and reinfection with H. pylori after successful eradication. To eradicate H. pylori infection, patients with active peptic ulcer disease were assigned to two treatment groups depending on the year of their enrollment (AM group and OAMR group). Patients in the AM group received 400 mg of cimetidine twice per day, 300 mg of amox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…That is, the eradication rate of per protocol (PP) analysis decreased up to 75.9% in 2006 [9]. Some studies reported that the recurrence of H. pylori infection more frequently occurred in patients treated with a low efficacy regimen than in those treated with a high efficacy regimen, as a result of recrudescence of the organism after temporary suppression, not elimination [14,16,22,23]. In the previous studies, the PP eradication rates were reported at 77.2% for the 7- and 93.6% for the 14 day EBMT regimen [24], and 83.8% for the 7-, 82.6% for the 10- and 79.9% for the 14 day MEA regimen [25].…”
Section: Discussionmentioning
confidence: 99%
“…That is, the eradication rate of per protocol (PP) analysis decreased up to 75.9% in 2006 [9]. Some studies reported that the recurrence of H. pylori infection more frequently occurred in patients treated with a low efficacy regimen than in those treated with a high efficacy regimen, as a result of recrudescence of the organism after temporary suppression, not elimination [14,16,22,23]. In the previous studies, the PP eradication rates were reported at 77.2% for the 7- and 93.6% for the 14 day EBMT regimen [24], and 83.8% for the 7-, 82.6% for the 10- and 79.9% for the 14 day MEA regimen [25].…”
Section: Discussionmentioning
confidence: 99%
“…4,5,9,38 Gastric Helicobacter spp have been identified in extragastric locations, such as the oral cavity (dental plaque, saliva, or gingival pockets), where they may be protected from antimicrobial therapy and could serve as a nidus for gastric recolonization and recrudescence of infection. 34,[39][40][41] Helicobacter pylori also can revert to a coccoid form after exposure to certain antibiotics. 34 It may not be possible to identify this form by routine laboratory techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Intermediate rates of reinfection are found in the Mediterranean region and Japan, ranging from 1.5% to 16.7%. 15,[28][29][30][31][32][33][34] It is sometimes difficult to distinguish between reinfection, defined as the complete eradication of an H. pylori infection followed by the introduction of a new H. pylori infection and recrudescence, defined as the apparent clearance of an H. pylori infection due to suppression but not eradication of the organism, followed by a positive test for H. pylori. 35 In our study, positive cultures after reinfection were obtained from only two of 14 reinfected patients and RAPD-PCR testing showed similarity to the strains present prior to treatment.…”
Section: Discussionmentioning
confidence: 99%